2019
DOI: 10.1111/ene.14050
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic hypotension as a risk factor for longitudinal deterioration of cognitive function in the elderly

Abstract: Background and purpose Orthostatic hypotension is frequent with aging with a prevalence of 20%–30% in people aged 65 or older and is considered to increase the risk for coronary events, strokes and dementia. Our objective was to characterize the association of orthostatic hypotension and cognitive function longitudinally over 6 years in a large cohort of the elderly aged over 50 years. Methods In all, 495 participants were assessed longitudinally with the Schellong test and comprehensive cognitive testing usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…45 It is generally believed that the COH of the elderly is related to the decline of cognitive function. Zimmermann et al 46 found that the executive and memory functions of elderly participants with COH deteriorated faster than those without COH. Cremer et al followed 7425 participants (aged 65 or above) for 12 years and observed a significant correlation between the presence of COH at baseline and the occurrence of dementia.…”
Section: Chd and CImentioning
confidence: 99%
“…45 It is generally believed that the COH of the elderly is related to the decline of cognitive function. Zimmermann et al 46 found that the executive and memory functions of elderly participants with COH deteriorated faster than those without COH. Cremer et al followed 7425 participants (aged 65 or above) for 12 years and observed a significant correlation between the presence of COH at baseline and the occurrence of dementia.…”
Section: Chd and CImentioning
confidence: 99%
“…Interestingly, the studies using more than one cognitive task were more likely to find an association between OH and worse cognition, while the use of a single neuropsychological tool may underestimate this association (38). Furthermore, in a large longitudinal cohort of elderly subjects aged over 50 years, participants with OH showed a faster deterioration in executive and memory functions and presented a higher vascular burden as compared to participants without OH (39). However, it is still unclear whether the association between OH and poorer cognitive performance is causal, even in a general middle-aged population.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it should not be overlooked that various medications such as alpha-blockers, anti-dementia drugs, antidepressants, opioids, antipsychotic drugs, and levodopa, which may often be used in the treatment of older people with dementia, and various comorbidities, such as HT, DM, frailty, and polypharmacy, may also play a role in the development of OH in older patients with dementia as well as in those without dementia [3, 11]. We found that following our adjustment by excluding these confounding factors in our cases, the risk of OH increased 2.23 times in AD, 3.68 times in DLB, and 3.56 times in VaD and that the risk of diastolic OH increased 4.19 times in VaD cases.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, OH is considered a risk factor for dementia and cognitive decline [3]. The most favorable proposed mechanism linking OH to dementia is the recurrent transient cerebral hypoperfusion hypothesis, which causes leukoaraiosis underlying the neurodegeneration process in dementia [11].…”
Section: Introductionmentioning
confidence: 99%